A Knowledge Graph to Understand Nursing Big Data: Case Example for Guidance. Issue 3 (3rd April 2021) - Hussey, Pamela; Das, Subhashis; Farrell, Sharon; Ledger, Lorraine; Spencer, Anne
Abstract: Purpose: To provide a summary of research on ontology development in the Centre of eIntegrated Care at Dublin City University, Ireland. Design: Design science methods using Open Innovation 2.0. Methods: This was a co‐participatory study focusing on adoption of health informatics standards and translation of nursing knowledge to advance nursing theory through a nursing knowledge graph (NKG). In this article we outline groundwork research conducted through a focused analysis to advance structural interoperability and to inform integrated care in Ireland. We provide illustrated details on a simple example of initial research available through open access. Findings: For this phase of development, the initial completed research is presented and discussed. Conclusions: We conclude by promoting the use of knowledge graphs for visualization of diverse knowledge translation, which can be used as a primer to gain valuable insights into nursing interventions to inform big data science in the future. Clinical Relevance: In line with stated global policy, the uptake and use of health informatics standards in design science within the profession of nursing is a priority. Nursing leaders should initially focus on health informatics standards relating to structural interoperability to inform development of NKGs. This will provide a robust foundation to gain valuable insights into articulating the nursing contribution in relation to the design of digital health and progress the nursing contribution to targeted data sources for the advancement of United Nations Sustainable Development Goal Three.